MENERAPKAN PEMBELAJARAN AKTIF UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR EKONOMI PESERTA DIDIK - Dewi Koryati; Dian Eka Amrina; Siti Fatimah; Dewi Pratita (Jurnal Profit Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2020)
To discuss conceptual economic materials, active learning techniques are very well used. How, by combining three methods of teaching (triple methods), namely; Simulation, discussion, and cooperative learning.This technique can also improve the motivation and outcome of economic learning, because learners play a direct role in learning and training their skills to solve economic problems. The research uses the one group pretest-posttest design. Data obtained through pretests and posttest and a questionnaire against 33 respondents in the class XI.2 Social Science,  High School.  Hypothesized test with the parametric test-T sample statically correlates.  Analysis results showed significant increases in learning outcomes after active learning. Students' understanding of the command economic system, the concept of the market, and the concept of opportunity cost with good value. Understanding the main problems of economic sciences, concepts and basic principles of productive efficiency, concepts and principles of the market economic system, and the concept of cost of opportunities for the most skilled workforce.  The learners ' ability to analyse the fundamental economic objectives of the Community and its relationship with the economy policy is less value.  The rate of motivation to study economics increased by 1.57%, but there was no significant increase in motivation after they had participated in active learning.  In order to implement improved learning techniques, the educators are encouraged to be able to manage the limited learning time in the classroom and take advantage of the various tools, materials, media, and learning resources relevant to the material Learning.AbstrakUntuk  membahas materi-materi ekonomi yang konseptual, teknik pembelajaran aktif sangat baik digunakan. Caranya, dengan menggabungkan tiga metode mengajar (triple methods), yaitu; simulasi, diskusi, dan belajar kooperatif.Teknik ini juga dapat meningkatkan motivasi dan hasil belajar ekonomi,karenapeserta didikberperan langsung dalam pembelajaran dandilatih kemahirannyauntuk memecahkan masalah-masalah ekonomi.Penelitian menggunakan the one group pre-test  post-test design. Data diperoleh melalui pretest dan posttest serta kuesioner terhadap 33 responden di kelas XI IPS 2 Sekolah Menengah Atas (SMA).Uji hipotesis dengan statistik parametris Uji-T Sampel Berkorelasi.Hasil analisismenunjukkan terdapat peningkatan hasil belajar yang signifikan setelah pembelajaran aktif.Pemahaman peserta didik tentang sistem ekonomi komando, konsep pasar, dan konsep biaya peluang terkatagori baik.Memahami permasalahan utama ilmu ekonomi, konsep dan prinsip dasar efisiensi produktif, konsep dan prinsip sistem ekonomi pasar, dan konsep biaya peluang untuk tenaga kerja terkatagori  cukup. Kemampuan peserta didik menganalisis tujuan-tujuan ekonomi dasar masyarakat dan hubungannya dengan kebijakan ekonomi terkatagorikurang.Rerata skor motivasi belajar ekonomi meningkat sebesar 1,57%, namun tidak ada peningkatan yang signifikan pada motivasi setelah mereka mengikuti pembelajaran aktif.  Agar dalam penerapan teknik pembelajaran aktif diperoleh hasil yang lebih baik, maka kepada pendidikdisarankan dapat mengelola waktu belajar yang terbatas dalam kelas dan memanfaatkan berbagai alat, bahan, media, dan sumber belajar yang relevan dengan materi pembelajaran.